Long-term migration of a bullet to the bladder after 47 years of trauma: A literature review - Bao Truong Phan; Vinh Vo Anh Trang; Sang Tan Tran; Huan Quang Le; Duy Hoai Nhat Nguyen; Vu Ngoc Anh Pham; Thien Tan Tri Tai Truyen (Urology Case Reports, 2025)
Foreign bodies in the urinary tract are uncommon and can arise from self-insertion or migration from other organs. Documented cases include various objects such as intrauterine devices, fragments of Foley catheters, toothpicks, and fish bones. However, the migration of bullet fragments into the urinary tract from another location is extremely rare with only a few cases reported in the current literature. Here, we present a case of a urinary tract stone formed around a foreign body—a bullet fragment—discovered 47 years after the patient experienced trauma.